Management of functional dyspepsia: state of the art and emerging therapies. (January 2018) - Yamawaki, Hiroshi; Futagami, Seiji; Wakabayashi, Mako; Sakasegawa, Noriko; Agawa, Shuhei; Higuchi, Kazutoshi; Kodaka, Yasuhiro; Iwakiri, Katsuhiko
Patients with functional dyspepsia, defined in the 2016 Rome IV criteria as bothersome clinical dyspepsia symptoms, experience markedly reduced quality of life. Several etiologies have been associated with the disorder. In the Rome IV criteria, the brain–gut axis was acknowledged as an important factor in the etiology of functional gastrointestinal (GI) disorders. The distinct subgroups of functional dyspepsia, epigastric pain syndrome (EPS) and postprandial distress syndrome (PDS), are treated differently: acid secretion inhibitors are recommended with patients with EPS, whereas prokinetic drugs as mosapride and acotiamide are recommended for patients with PDS. A previous study has reported that proton pump inhibitors (PPIs) and H2 -blockers were equally effective in functional dyspepsia. A new drug, acotiamide, a muscarinic antagonist and cholinesterase inhibitor, has been shown to improve gastric motility in rodents and dogs, and to reduce PDS symptoms in patients in double-blind multicenter studies. The pharmacological mechanisms of acotiamide remain unknown; whether acotiamide alters gastric emptying and gastric accommodation in patients with functional dyspepsia remains an open question. Other emerging treatment options include Rikkunshito, a herbal medicine that improves gastric emptying through 5-hydroxytryptamine (5-HT)2B-mediated pharmacological action, and tricyclic antidepressants (TCAs). Different drugs are needed to accommodate the clinical symptoms and etiology in individual patients.